(untitled) (Revista Argentina de Cirugía, 2026)
Transoral endoscopic thyroidectomy/parathyroidectomy vestibular approach is a scarless alternative to open surgery. Atypical parathyroid tumors account for 1% of primary hyperparathyroidism cases. Fluorescence-guided surgery is a method that allows surgeons to locate and precisely identify the parathyroid glands, thus facilitating their dissection. We report the case of a 29-year-old female patient diagnosed with primary hyperparathyroidism and an indeterminate thyroid nodule located on the same side. The patient underwent transoral endoscopic vestibular approach combined with indocyanine green angiography to localize the parathyroid glands using near infrared light and compare the overlay view with the white light view. The procedure involved parathyroidectomy and ipsilateral hemithyroidectomy, without complications. The pathological examination reported an atypical adenoma and a benign thyroid nodule. One month after surgery, calcemia and parathormone levels remained normal.